ANALYSIS OF MUSIC IN ISLAMIC LAW PERSPECTIVE - Ubabuddin Ubabuddin; Mohd. Faeez Bin Ilias; Herwani Herwani (Realism: Law Review, 2025)
In Islamic history, music is known for its three elements which are called handasah al-sawt, al-musiqa, and ghina. Referring to Isma'il and Al-Faruqi's Lois Lam, Abdul Hadi said that music that is in line with Islamic goals is handasah al-sawt whose contents are manifestations of Muslim aesthetics originating from Islamic tradition, whose implementation rules are rooted in the aesthetics of the Qur'an. According to an Islamic perspective, music that is required by syara' can be used as a tool to educate while entertaining, namely through an Islamic approach. Entertainment that meets entertainment standards in Islam is entertainment that inspires enthusiasm and awareness towards remembering Allah as well as educating people to live up to Islamic teachings. Abdul Ghani An-Nabalisiy, said that music law was initially halal. Whatever the form, both the kind of music that is peaceful and that which is hit. It's not only halal, it's not even seen as bad in common sense and custom. Its prohibition emerged when the ulema began to see the facts of the bad effects of music, for example, making the audience forget Allah and neglect worship. In general, when music leads to disobedience and futility, that's when it starts to be forbidden. So it's important to put it back that music is basically a medium. As a medium, music cannot be judged by anything.